The effect of PLISSIT based counseling model on sexual function, quality of life, and sexual distress in women surviving breast cancer: a single-group pretest-posttest trial - Zohreh Keshavarz; Elham Karimi; Samira Golezar; Giti Ozgoli; Maliheh Nasiri (BMC, 2021)
Abstract Background Diagnosis and treatment of breast cancer potentially leads to sexual dysfunction and sexual distress in women and negatively affects their quality of life (QoL). This study aimed at determining the effect of PLISSIT based counseling on sexual function, sexual distress, and QoL in women surviving breast cancer. Methods In this pre-test, post-test, single-group semi-experimental study, 65 women surviving breast cancer who were referred to the selected centers were included in the study via the available sampling method. Data gathering tools included a researcher-made demographic questionnaire, female sexual function index, beck depression inventory-II, State‐Trait Anxiety Inventory, World Health Organization QoL-Brief, and Female Sexual Distress Scale-Revised. The counseling program (7 sessions 60 min each) was designed based on the PLISSIT model. The sexual function, sexual distress, and QoL were evaluated before, and 2 and 4 weeks after the intervention. To compare the mean scores of variables before and after the intervention, repeated-measured ANOVA was used. Results The findings showed that PLISSIT based counseling significantly reduced sexual distress and increased the scores of QoL and all its domains, as well as sexual function and all its domains in women surviving breast cancer (p < 0.05). There was no significant difference in the mean scores of variables 2 and 4 weeks after the intervention. Conclusions It seems that PLISSIT based counseling reduces sexual dysfunction and sexual distress and improves the QoL of women surviving breast cancer. So, it is recommended that these counseling programs be integrated into the health care program of this group of women. Trial registration TCTR202103170010, 17 March 2021, Retrospectively registered, at https://www.thaiclinicaltrials.org/ .